A kind of magnetized graphene-nano silicate gel and preparation method thereof
By using magnetized graphene-nano silicate gel, the problem of difficulty in improving the early strength and working properties of concrete at the same time is solved, and the high early strength and good working properties of concrete are achieved, reducing the risk of separation.
Patent Information
- Application Number
- CN202311417222.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-10-30
AI Technical Summary
The prior art is difficult to improve the early strength and working properties of concrete at the same time, resulting in segregation and slurry separation of concrete during pumping.
Using magnetized graphene-nanosilicate gel, polycondensation with a network structure is prepared by combining nanosilicon oxide, ultrafine powder grinding clinker, orthosiliic acid, graphene, silane coupling agent and nanocellulose. Silicic acid gel to enhance the cohesiveness and early strength of concrete.
It significantly improves the early strength and working properties of concrete, reduces the possibility of separation, and improves the flexural properties and flowability of concrete.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicate gel, and in particular to a magnetized graphene-nano silicate gel. Background Art
[0002] In the ready-mixed concrete industry, there is a lack of reusable admixtures that can effectively improve the workability and early strength of concrete at the same time. Organic admixtures such as early strength agents and viscosity adjusters can only be used according to the needs of both. The use of organic admixtures for adjustment is often limited by raw materials. When the raw materials of concrete change, the organic admixture and the original concrete mix ratio will be incompatible. By adjusting the admixture to control the workability, it is easy to cause the material to stick, workers to add water on site, or concrete segregation and slurry separation, resulting in poor workability and difficulty in pumping. Therefore, it is necessary to design a product that can effectively improve the early strength and workability of concrete at the same time. Summary of the invention
[0003] The technical problem to be solved by the present invention is: the present invention proposes a nano silicate gel and a preparation method thereof to solve the problem that the cohesiveness and early strength of concrete are difficult to adjust and greatly reduce the possibility of concrete segregation.
[0004] The technical scheme of the present invention is: a magnetized graphene-nanosilicate gel, which comprises, by weight, 19-29 parts of nano silicon oxide, 74-116 parts of ultrafine powder clinker, 26-32 parts of orthosilicic acid, 1200-1800 parts of deionized water, 0.3-0.5 parts of dissolving agent, 0.7-1.3 parts of graphene, 11-25 parts of silane coupling agent and 24-36 parts of nano cellulose.
[0005] Preferably, the nano silicon oxide is prepared by a sol-gel method, has a particle size between 20 and 60 nm, a purity of 99%, and is used in an amount of 22 to 26 parts.
[0006] Preferably, the ultrafine ground clinker includes one or more of ground tricalcium silicate and ground dicalcium silicate, wherein the ground tricalcium silicate is obtained by grinding tricalcium silicate with a high fine grinding mill, with a fineness of 8 to 15 microns and a purity of 99%; the ground dicalcium silicate is obtained by grinding dicalcium silicate with a high fine grinding mill, with a fineness of 8 to 15 microns and a purity of 99%, and the dosage is 84 to 106 parts.
[0007] Preferably, the dissolving agent is one or more of CuSO4, FeSO4, and Na2SO4.
[0008] Preferably, the amount of graphene is 0.9 to 1.1 parts.
[0009] Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane, and the amount used is 14 to 22 parts.
[0010] Preferably, the nanocellulose has a width of 20-50 nm, a length of 0.8-2 micrometers, a purity of 99%, and a dosage of 29-31 parts.
[0011] The deionized water is pure water that is treated and does not contain ionic substances.
[0012] The preparation method of magnetized graphene-nano silicate gel comprises the following steps:
[0013] Step 1: Weigh the amount of each component according to the mass ratio, put the nano-silicon oxide and ultra-fine ground clinker into a planetary mixer and stir for 15 seconds, add 20-25 parts of deionized water into the planetary mixer and stir for 150 seconds to obtain a gelling component slurry. After the slurry is allowed to stand for 240 seconds, 575-780 parts of deionized water and orthosilicic acid are added while stirring the slurry. After the feeding is completed, stir for more than 300 seconds to obtain an initial silicate gel, and let the initial silicate gel stand for 150 minutes; during this process, the ultra-fine ground clinker undergoes a hydration reaction to generate calcium hydroxide and hydrated calcium silicate gel, and the nano-silicon oxide reacts with the product Calcium hydroxide can undergo a secondary reaction to generate hydrated calcium silicate gel, which can consume part of calcium hydroxide while increasing the formation of calcium silicate products, thereby increasing the concentration of hydrated calcium silicate gel; at the same time, after adding orthosilicic acid, on the one hand, the residual calcium hydroxide can be consumed to form hydrated calcium silicate gel, and on the other hand, the excess orthosilicic acid is dissolved and dispersed between the clinker particles and the hydrated calcium silicate products, and undergoes a polycondensation reaction in the deionized water medium to form a polycondensed silicate with a network structure. The structure has a strong water retention performance, which increases the surface tension of the hydrated calcium silicate gel suspension and forms a state with non-Newtonian fluid characteristics. In order to prevent the calcium silicate gel formed during the entire hydration reaction process from overlapping each other to form a continuous strength structural unit, more deionized water is added and continuously stirred to disperse the hydrated calcium silicate products to form separate nano-hydrated calcium silicate. The polycondensed silicate in the suspension keeps the clinker and hydrated calcium silicate that have not yet reacted in a dispersed state, thereby avoiding the overlapping of subsequent hydration reaction products to form a large particle structure.
[0014] Step 2: Stirring the initial silicate gel after standing at a speed of 300 r / min, adding a dissolving agent dropwise at a uniform speed during the stirring, and controlling the dropping time to be 30-35 min to obtain a dissolved silicate gel, and at the same time, adding the nanocellulose into 600-1000 parts of deionized water and stirring to dissolve, to obtain a nanocellulose solution;
[0015] Step 3: Add the nanocellulose solution to the dissolved silicate gel, stir at a speed of 500r / min for 60s, then put the silane coupling agent into the mixer and continue stirring for 120s to obtain a nanosilicate gel suspension, put graphene into the suspension, stir evenly at a speed of 30r / min, and place the suspension in a magnetic field of 900~1200G for magnetization for 120min. After the magnetization is completed, let the suspension stand for 24h and then use a filter press to filter out excess water, put the filtered product into an oven, set the oven temperature at 60~80℃, and bake for 48h to obtain magnetized graphene-nanosilicate gel powder.
[0016] During step 2 and step 3, the dissolving agent absorbs the free calcium in the suspension, further improving the purity of the reaction product. In the aqueous medium, the ethoxysilane group of the silane coupling agent is hydrolyzed to form silanol. The surface of the nanocellulose contains a large number of hydroxyl groups. The silanol undergoes a condensation reaction with the hydroxyl group to form a stable covalent bond. The unreacted hydroxyl groups on the surface of the nanocellulose are adsorbed on the surface of the hydrated calcium silicate gel. In addition, the magnetized graphene is oxidized by the hydroxyl groups on the surface of the nanocellulose under the action of magnetic force to form graphene oxide, which is evenly distributed in every corner of the suspension. After drying at a specific temperature, a magnetized graphene-nanosilicate gel with the ability to adjust the cohesiveness and early strength of concrete is obtained.
[0017] Application of magnetized graphene-nanosilicate gel in concrete.
[0018] The beneficial effects of the present invention are:
[0019] 1. In addition to the formation of hydrated calcium silicate, a large amount of calcium hydroxide products are also generated during the hydration reaction of ultrafine ground clinker. The addition of calcium hydroxide to concrete will destroy the effect of the water reducer, thereby increasing the loss of concrete workability. Therefore, in the present invention, while generating hydrated calcium silicate through the reaction of nano-silicon oxide and orthosilicic acid with calcium hydroxide, most of the excess calcium hydroxide is consumed. Sulfate is used as a dissolving agent to further consume the residual calcium hydroxide to generate harmless micro-soluble calcium sulfate, thereby improving the purity of the silicate gel in the suspension;
[0020] 2. Add the magnetized graphene-nano calcium silicate hydrate gel powder into the concrete. After sufficient stirring, the magnetized graphene-nano calcium silicate hydrate gel particles are evenly dispersed in the concrete paste. The silanol end of the silane coupling agent and the nanocellulose are adsorbed on the surface of the nano calcium silicate hydrate. The large number of hydroxyl groups on the surface of the nanocellulose increase the hydrogen bonding force of water molecules, thereby making the concrete paste more viscous. The network structure formed by the polysilicic acid attached to the surrounding reduces the flow between water molecules, thereby improving the viscosity of the entire concrete fluid.
[0021] 3. After the magnetized graphene-nano hydrated calcium silicate gel powder is added to the concrete, the nano calcium silicate gel particles evenly dispersed in the concrete slurry can give full play to the "induced molding" effect. The strength structure formed by the hydration of the cementitious material slurry in the concrete can be quickly formed on the nano calcium silicate gel particles and connected to each other to form strength. At the same time, the composition of the nano calcium silicate gel particles is the same as the component of the hydration product of the concrete cementitious material slurry. The nano calcium silicate gel can be well filled into the gaps formed after the concrete hardens, reducing the generation of micro cracks, effectively improving the early strength of the concrete while reducing the possibility of concrete cracking;
[0022] 4. As the hydration reaction of the concrete paste proceeds, the alkalinity inside the concrete increases, and the nanocellulose is no longer adsorbed on the surface of the nanosilicate gel. The nanocellulose in the concrete paste undergoes a polycondensation reaction in an alkaline environment to form long-chain fiber macromolecules, which are distributed in the strength structure of the hardened concrete. At the same time, the magnetized graphene reacts under the action of hydroxyl groups and magnetic force to form graphene oxide. The dispersibility of graphene oxide is much higher than that of graphene. When in the concrete paste, under the superposition of its "dispersion effect + magnetic effect", the magnetized graphene can be evenly distributed inside the concrete. Both fiber macromolecules and graphene are materials with high toughness and high tensile strength. Under the dual action of fiber macromolecules and magnetized graphene, the toughness of concrete can be greatly improved, and the flexural performance of concrete can be improved. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below through specific implementation examples, which are intended to explain the present invention rather than to limit it.
[0024] Example 1: Preparation of a magnetized graphene-nanosilicate gel, the steps are as follows:
[0025] (1) By mass: 19 parts of nano-silicon oxide and 74 parts of ultrafine ground clinker were added into a planetary mixer and stirred for 15 seconds. 20 parts of deionized water were added into the planetary mixer and stirred for 150 seconds to obtain a gelling component slurry. After the slurry was allowed to stand for 240 seconds, 580 parts of deionized water and 26 parts of orthosilicic acid were added while stirring the slurry. After the addition of the materials was completed, the mixture was stirred for more than 300 seconds to obtain an initial silicate gel. The initial silicate gel was allowed to stand for 150 minutes.
[0026] (2) The initial silicate gel after standing in step (1) was stirred at a speed of 300 r / min, and 0.4 parts of dissolving agent was added dropwise at a uniform rate, and the dropping time was controlled to be 30-35 minutes to obtain a dissolved silicate gel. At the same time, 24 parts of nanocellulose were added into 680 parts of deionized water and stirred to dissolve to obtain a nanocellulose solution.
[0027] (3) Add the nanocellulose solution in step (2) to the dissolved silicate gel, stir at a speed of 500 r / min for 60 seconds, then add 11 parts of silane coupling agent into a mixer and continue stirring for 120 seconds to obtain a nanosilicate gel suspension, add 0.7 parts of graphene into the suspension, stir evenly at a speed of 30 r / min, and place the suspension in a magnetic field of 900~1200G for magnetization for 120 minutes. After the magnetization is completed, the suspension is allowed to stand for 24 hours and then the excess water is filtered out by a filter press, and the filtered product is placed in an oven with the oven temperature set at 60~80°C. After baking for 48 hours, the magnetized graphene-nanosilicate gel powder is obtained.
[0028] Example 2: Preparation of a magnetized graphene-nano silicate gel, the steps are as follows:
[0029] (1) By mass: 22 parts of nano-silicon oxide and 84 parts of ultrafine ground clinker were added into a planetary mixer and stirred for 15 seconds. 22 parts of deionized water were added into the planetary mixer and stirred for 150 seconds to obtain a gelling component slurry. After the slurry was allowed to stand for 240 seconds, 640 parts of deionized water and 28 parts of orthosilicic acid were added while stirring the slurry. After the addition of the materials was completed, the mixture was stirred for more than 300 seconds to obtain an initial silicate gel. The initial silicate gel was allowed to stand for 150 minutes.
[0030] (2) The initial silicate gel after standing in step (1) was stirred at a speed of 300 r / min, and 0.4 parts of dissolving agent was uniformly added dropwise, and the dropping time was controlled to be 30-35 minutes to obtain a dissolved silicate gel. At the same time, 29 parts of nanocellulose were added into 738 parts of deionized water and stirred to dissolve, thereby obtaining a nanocellulose solution.
[0031] (3) Add the nanocellulose solution in step (2) to the dissolved silicate gel, stir at a speed of 500 r / min for 60 seconds, then add 14 parts of silane coupling agent into a mixer and continue stirring for 120 seconds to obtain a nanosilicate gel suspension, add 0.9 parts of graphene into the suspension, stir evenly at a speed of 30 r / min, and place the suspension in a magnetic field of 900~1200G for magnetization for 120 minutes. After the magnetization is completed, the suspension is allowed to stand for 24 hours and then the excess water is filtered out by a filter press, and the filtered product is placed in an oven at a temperature of 60~80°C, and baked for 48 hours to obtain a magnetized graphene-nanosilicate gel powder.
[0032] Example 3: Preparation of a magnetized graphene-nano silicate gel, the steps are as follows:
[0033] (1) By mass: 26 parts of nano-silicon oxide and 106 parts of ultrafine ground clinker were added into a planetary mixer and stirred for 15 seconds. 24 parts of deionized water were added into the planetary mixer and stirred for 150 seconds to obtain a gelling component slurry. After the slurry was allowed to stand for 240 seconds, 720 parts of deionized water and 30 parts of orthosilicic acid were added while stirring the slurry. After the addition of the materials was completed, the mixture was stirred for more than 300 seconds to obtain an initial silicate gel. The initial silicate gel was allowed to stand for 150 minutes.
[0034] (2) The initial silicate gel after standing in step (1) was stirred at a speed of 300 r / min, and 0.4 parts of dissolving agent was added dropwise at a uniform rate, and the adding time was controlled to be 30-35 minutes to obtain a dissolved silicate gel. At the same time, 31 parts of nanocellulose were added to 856 parts of deionized water and stirred to dissolve to obtain a nanocellulose solution.
[0035] (3) Add the nanocellulose solution in step (2) to the dissolved silicate gel, stir at a speed of 500 r / min for 60 seconds, then add 22 parts of silane coupling agent into a mixer and continue stirring for 120 seconds to obtain a nanosilicate gel suspension, add 1.1 parts of graphene into the suspension, stir evenly at a speed of 30 r / min, and place the suspension in a magnetic field of 900~1200G for magnetization for 120 minutes. After the magnetization is completed, the suspension is allowed to stand for 24 hours and then the excess water is filtered out by a filter press, and the filtered product is placed in an oven with the oven temperature set at 60~80°C. After baking for 48 hours, the magnetized graphene-nanosilicate gel powder is obtained.
[0036] Example 4: Preparation of a magnetized graphene-nanosilicate gel, the steps are as follows:
[0037] (1) By mass: 29 parts of nano-silicon oxide and 116 parts of ultrafine ground clinker were added into a planetary mixer and stirred for 15 seconds. 25 parts of deionized water were added into the planetary mixer and stirred for 150 seconds to obtain a gelling component slurry. After the slurry was allowed to stand for 240 seconds, 780 parts of deionized water and 32 parts of orthosilicic acid were added while stirring the slurry. After the addition of the materials was completed, the mixture was stirred for more than 300 seconds to obtain an initial silicate gel. The initial silicate gel was allowed to stand for 150 minutes.
[0038] (2) The initial silicate gel after standing in step (1) was stirred at a speed of 300 r / min, and 0.4 parts of dissolving agent was added dropwise at a uniform rate, and the adding time was controlled to be 30-35 minutes to obtain a dissolved silicate gel. At the same time, 36 parts of nanocellulose were added into 995 parts of deionized water and stirred to dissolve, thereby obtaining a nanocellulose solution.
[0039] (3) Add the nanocellulose solution in step (2) to the dissolved silicate gel, stir at a speed of 500 r / min for 60 seconds, then add 25 parts of silane coupling agent into a mixer and continue stirring for 120 seconds to obtain a nanosilicate gel suspension, add 1.3 parts of graphene into the suspension, stir evenly at a speed of 30 r / min, and place the suspension in a magnetic field of 900~1200G for magnetization for 120 minutes. After the magnetization is completed, the suspension is allowed to stand for 24 hours and then the excess water is filtered out by a filter press, and the filtered product is placed in an oven with the oven temperature set at 60~80°C. After baking for 48 hours, the magnetized graphene-nanosilicate gel powder is obtained.
[0040] The magnetized graphene-nano silicate gel prepared in Examples 1 to 4 was added to C30 and C60 concretes at a cementitious material ratio of 5%, and the concrete mix ratios were shown in the following table by mass:
[0041] Table 1 Concrete mix ratio
[0042] cement Mineral powder Fly ash gravel Machine-made sand water Magnetized graphene-nanosilicate gel C30 190 40 90 940 900 160 16 C60 280 60 80 1020 890 135 21
[0043] A comparative example 1 is set, which differs from the example 3 in that the addition of graphene and the magnetization process are removed, and the other components and processes are the same.
[0044] In addition, a control group was set up, control group 1 was C30 concrete without nano silicate gel, and control group 2 was C60 concrete without nano silicate gel. Their properties are shown in Table 2 and Table 3, and the strength unit is MPa:
[0045] Table 2 Performance indexes of C30 concrete
[0046] 1d compressive strength 7d compressive strength 28d compressive strength 1d flexural strength 7d flexural strength 28d flexural strength Anti-segregation rate% Slump / expansion mm Control group 1 4.2 25.3 34.6 0.6 3.1 4.7 84 220 / 530 Example 1 16.6 31.4 36.4 2.2 4.1 5.8 93 270 / 620 Example 2 18.2 31.7 37.9 2.9 4.7 6.4 98 280 / 650 Example 3 18.7 32.4 36.4 3.1 4.7 6.6 99 260 / 610 Example 4 18.9 32.8 37.2 3.3 4.8 6.9 99 225 / 545 Comparative Example 1 17.7 34.9 38.2 1.8 3.5 5.6 99 260 / 650
[0047] Table 3 Performance indexes of C60 concrete
[0048] 1d compressive strength 7d compressive strength 28d compressive strength 1d flexural strength 7d flexural strength 28d flexural strength Anti-segregation rate% Slump / expansion mm Control group 2 12.3 51.2 68.4 1.9 6.6 8.2 91 240 / 560 Example 1 26.8 58.4 70.3 5.6 9.1 10.8 97 270 / 610 Example 2 32.6 60.3 72.7 7.4 10.4 12.3 99 280 / 640 Example 3 33.1 61.5 72.9 7.7 11.2 12.7 99 280 / 635 Example 4 33.3 61.9 71.7 7.7 11.6 12.6 99 250 / 570 Comparative Example 1 32.8 62.5 73.3 6.2 9.2 10.8 99 275 / 680
[0049] From the results in Tables 2 and 3, it can be seen that, whether it is C30 or C60 grade concrete, after adding magnetized graphene-nanosilicate gel, the early strength (1d and 7d) of concrete is greatly improved. For example, compared with control group 1 and control group 2, in Example 3, the 1d compressive strength of C30 and C60 concrete increased by 345% and 169%, respectively. At the same time, under the condition of greatly improved early strength, its later strength is not lower than that of the control group. And under the action of nanocellulose and magnetized graphene, the flexural strength of concrete is greatly improved. Compared with control group 1 and control group 2, in Example 3, the 1d flexural strength of C30 and C60 concrete increased by 300% and 305%, respectively.
[0050] In Comparative Example 1 after removing the graphene and magnetization process, compared with Example 3, the 7d and 28d compressive strength of C30 is slightly improved, but the full-age flexural strength is reduced, and the 1d flexural strength of C30 and C60 concrete is reduced by 26% and 19%, respectively. This shows that the magnetized graphene-nanosilicate gel obtained after the introduction of graphene and the magnetization process can further improve the flexural strength of concrete.
[0051] After adding the magnetized graphene-nanosilicate gel, the cohesiveness and water retention of the concrete are improved. Therefore, the anti-segregation rate of the concrete is also greatly improved. In Examples 3-4, the anti-segregation rates of C30 and C60 concretes both reach 99%.
[0052] Comprehensive comparison shows that when the formula value of nanosilicate gel is lower than the preferred range, the effect of improving early strength and workability are not as good as those within the preferred range; when it is higher than the preferred range, the strength of concrete is not lower than the preferred range, but the slump and expansion drop rapidly, and its fluidity is far lower than the preferred range.
[0053] Comprehensive comparison shows that when the formula value of nanosilicate gel is lower than the preferred range, the effect of improving early strength and workability are not as good as those within the preferred range; when it is higher than the preferred range, the strength of concrete is not lower than the preferred range, but the slump and expansion drop rapidly, and its fluidity is far lower than the preferred range.
[0054] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A magnetized graphene-nanosilicate gel, characterized in that: Calculated by weight, it includes 19-29 parts of nano silicon oxide, 74-116 parts of ultrafine powder clinker, 26-32 parts of ortho silicic acid, 1200-1800 parts of deionized water, 0.3-0.5 parts of dissolving agent, 0.7-1.3 parts of graphene, 11-25 parts of silane coupling agent, and 24-36 parts of nano cellulose, wherein the dissolving agent is one or more of CuSO4, FeSO4, and Na2SO4.
2. The magnetized graphene-nanosilicate gel according to claim 1, characterized in that: The nano silicon oxide is prepared by a sol-gel method, has a particle size between 20 and 60 nm, a purity of 99%, and is used in an amount of 22 to 26 parts.
3. The magnetized graphene-nanosilicate gel according to claim 1, characterized in that: The ultrafine ground clinker includes one or more of ground tricalcium silicate and ground dicalcium silicate, wherein the ground tricalcium silicate is obtained by grinding tricalcium silicate with a high-fine grinding mill, with a fineness of 8 to 15 microns and a purity of 99%; the ground dicalcium silicate is obtained by grinding dicalcium silicate with a high-fine grinding mill, with a fineness of 8 to 15 microns and a purity of 99%, and the dosage is 84 to 106 parts.
4. The magnetized graphene-nanosilicate gel according to claim 1, characterized in that: The graphene is used in an amount of 0.9 to 1.1 parts.
5. The magnetized graphene-nanosilicate gel according to claim 1, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane, and the dosage is 14-22 parts.
6. The magnetized graphene-nanosilicate gel according to claim 1, characterized in that: The nanocellulose has a width of 20-50 nm, a length of 0.8-2 microns, a purity of 99%, and a dosage of 29-31 parts.
7. A method for preparing a magnetized graphene-nanosilicate gel according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Weigh the amount of each component according to the mass ratio, put the nano-silicon oxide and ultrafine ground clinker into a planetary mixer and stir for 15 seconds, add 20-25 parts of deionized water into the planetary mixer and stir for 150 seconds to obtain a gelling component slurry, let the slurry stand for 240 seconds, add 575-780 parts of deionized water and orthosilicic acid while stirring the slurry, stir for more than 300 seconds after the feeding is completed, obtain an initial silicate gel, and let the initial silicate gel stand for 150 minutes; Step 2: Stirring the initial silicate gel after standing at a speed of 300 r / min, adding a dissolving agent dropwise at a uniform speed during the stirring, and controlling the dropping time to be 30-35 min to obtain a dissolved silicate gel, and at the same time, adding the nanocellulose into 600-1000 parts of deionized water and stirring to dissolve, to obtain a nanocellulose solution; Step 3: Add the nanocellulose solution to the dissolved silicate gel, stir at a speed of 500r / min for 60s, then put the silane coupling agent into the mixer and continue stirring for 120s to obtain a nanosilicate gel suspension, put graphene into the suspension, stir evenly at a speed of 30r / min, and place the suspension in a magnetic field of 900~1200G for magnetization for 120min. After the magnetization is completed, let the suspension stand for 24h and then use a filter press to filter out excess water, put the filtered product into an oven, set the oven temperature at 60~80℃, and bake for 48h to obtain magnetized graphene-nanosilicate gel powder.
8. Use of the magnetized graphene-nanosilicate gel according to any one of claims 1 to 6 in concrete.
Citation Information
Patent Citations
Calcium silicate hydrate gel solution early strength agent and preparation method thereof
CN104402009A
Calcium silicate hydrate gel solution early strength agent and preparation method thereof
CN104402288A